Design and Application of Additive Manufacturing (2022)
Additive manufacturing (AM) is continuously improving and offering innovative alternatives to conventional manufacturing techniques. The advantages of AM (design freedom, reduction in material waste, low-cost prototyping, etc.) can be exploited in different sectors by replacing or complementing traditional manufacturing methods. For this to happen, the combination of design, materials and technology must be deeply analyzed for every specific application. Despite the continuous progress of AM, there is still a need for further investigation in terms of design and applications to boost AM's implementation in the manufacturing industry or even in other sectors where short and personalized series productions could be useful, such as the medical sector. This Special Issue gathers a variety of research articles (12 peer-reviewed papers) involving the design and application of AM, including innovative design approaches where AM is applied to improve conventional methods or currently used techniques, design and modeling methodologies for specific AM applications, design optimization and new methods for the quality control and calibration of simulation methods.